Childhood obesity in the state of Paraná after the pandemic: a nutritional view (Research, Society and Development, 2023)
Childhood obesity is a serious public health problem that not only affects children's well-being, but also has long-term negative implications on their physical and mental health. The objective was to analyze the percentage of obese child patients in the state of Paraná between 2018 and 2022. Observational, cross-sectional study, with a quantitative approach and descriptive nature, carried out using data from children under 5 years old registered in SISVAN between 2018 and 2022 for the state of Paraná. The following variables were collected: gender, ethnicity, food consumption profile and nutritional status. Considering the total population at this age, information coverage in Brazil ranged from 26.5% to 44.2% and in Paraná from 27.7% to 48.1%. In Brazil, there was an increase in the number of children who were thin and eutrophic (+7.1% and +3.8%) and a decrease in those who were overweight and obese (-8.1% and -7.8%). %). In the state of Paraná there was an increase in the number of lean individuals (+23%) and eutrophic individuals (+2.7%), a decrease in the overweight rate (-11.8%) and an increase in those who were obese (+9.6%). %). The obesity rate increased by 12.2% in females and 10.6% in males. The black and indigenous populations showed a higher rate of variation for thinness (+25% and +20%, respectively) and obesity (+30% and 22%, respectively). There was an increase in the consumption of products with high calorie content, including hamburgers and/or sausages (+24.3%) followed by instant noodles, packaged snacks or savory biscuits (+19.1%).